Saline alkali water desalination project in Southern Xinjiang of China: A review of desalination planning, desalination schemes and economic analysis. (October 2019) - Fang, Shibiao; Tu, Wenrong; Mu, Lin; Sun, Zhilin; Hu, Qiuyue; Yang, Yang
Abstract: Solar desalination technology develops slowly in Southern Xinjiang, and salt-leaching method is the most popular measure for improving salinization land, failing to make full use of the local rich solar energy. Therefore, government of China plans to exploit the solar energy for driving the desalination process in Southern Xinjiang to solve the issue of water scarcity and salinization. Firstly, this paper reviews the existing status of salinization, and elaborates traditional treatment measures of salinization in Southern Xinjiang. Secondly, a saline alkali water desalination planning in Southern Xinjiang is demonstrated with detailed explication, showing the necessities and feasible strategy of the desalination project in Southern Xinjiang. Thirdly, a combination of reverse osmosis membrane and solar still is proposed for the desalination project, and current research states and progresses of membrane treatment technology and solar desalination are analysed, pointing out the possible solutions for research challenges in Southern Xinjiang. Finally, the technology of modifications of single basin solar still is studied, and several solar still configurations are selected from reference to conduct the cost analysis using local market price to figure out the optimal type suitable for Southern Xinjiang. Once this desalination project is implemented successfully, remedied saline lands in Xinjiang will become backup land resources to secure the local socio-economic and agricultural development, improving the ecological environment and soil fertility. Other prospective regions in China, such as eastern coastal saline soil, salted soil in North China Plain and Northeast Plain, can benefit from this research. Highlights: The status quo of salinization in Southern Xinjiang of China was investigated. Analysis of necessities of desalination project for agricultural development in China. Presentation of specified schemes in Southern Xinjiang's desalination project. Estimation of the water production cost for different types of solar stills. Presentation of economic benefits of desalination project in Southern Xinjiang.